Characteristics of Cyberaggression among College Student Minorities: Exploring Pervasiveness and Impact through Mixed-Methods - Oblad, Timothy; Trejos-Castillo, Elizabeth; Massengale, Elizabeth (International Journal of Criminology and Sociology, 2017)
Despite proximity to researchers, minority college students have not been well represented in cyber-aggressive studies. The present cross-cultural study uses mixed-methods to better understand how emerging adults are impacted from cyberbullying experiences (victims and/or bullies). All students (N=1,110) were between 18-25 years (m=20.5) with close to 50% being Hispanic (N=532). Results indicate self-control and self-esteem are important predictors in cyberbullying involvement, particularly among Hispanic cybervictims. Depression and suicidal ideation also served as significant predictors in involvement for cybervictimization. Through open-ended and coded responses, several themes emerged, such as being unable to focus on academics, avoiding individuals or groups because of victimization, low self-esteem, and loss of trust. Results and implications are discussed as well as recommendations for future research.